SUMBANGSI TEOLOGI ABRAHAM KUYPER BAGI KEADILAN SOSIAL DI INDONESIA: Sebuah Refleksi Iman Kristen - Irawati, Chandra Wahyuni (Didache: Jurnal Teologi dan Pendidikan Kristen, 2023)
The idea of Indonesian democracy is to fight for social justice for all Indonesians. Although the vision of social justice has long been echoed and fought for by the Indonesian people and has even been contained in detail in the state constitution, it has not yet been properly realized. The reality of social justice and welfare has not been realized for all, and economic disparity still exists in Indonesian society. One of the Christian theologians who focused on the framework for social and political reform is Abraham Kuyper. Using the literature research method, this paper investigates Kuyper's ideas and examines his contributions to social reform in the pursuit of social justice in Indonesia. Kuyper's vision is based on God's sovereignty over all aspects of life, which He has also delegated to humans, at least through the state, society, and the church.   Cita-cita demokrasi Indonesia adalah memperjuangkan keadilan sosial bagi seluruh rakyat Indonesia. Meskipun visi tentang keadilan sosial telah lama bergelora dan diperjuangkan oleh bangsa Indonesia bahkan telah termuat secara rinci dalam konstitusi negara namun belum terwujud dengan baik. Realita keadilan dan kesejahteraan sosial belum terwujud bagi semua, dan kesenjangan ekonomi masih terjadi dalam masyarakat Indonesia. Salah satu teolog Kristen yang berfokus pada kerangka berpikir bagi pembaruan di bidang sosial dan politik adalah Abraham Kuyper. Dengan menggunakan metode riset literatur, tulisan ini mengkaji pemikiran Kuyper dan melihat sumbangsihnya bagi pembaharuan sosial dalam mewujudkan keadilan sosial di Indonesia. Visi Kuyper berpusat pada kedaulatan Allah atas semua aspek kehidupan yang juga mendelegasikan otoritas-Nya kepada manusia, setidaknya melalui negara, masyarakat, dan gereja.